Una teoría para nada fuera de lo común. Teoría de roles: en las antípodas de la civilización del derecho penal - Lamas, Felipe (2015)
The following essay presents a critical analysis of the theory of crime designed by Günther Jakobs from the violation of established normative roles; indicating those notions which, in our opinion, are impossible to accept as fundamental pillars of a supposed objective theory which then must be applied to social reality.